Spontaneous Perforation as a First Presentation of Ileal Gastrointestinal Stromal Tumour (GIST) with Synchronous Breast Sarcoma - Bir Kumar Sharma M. (Journal of Clinical and Diagnostic Research, 2014)
Gastrointestinal Stromal Tumours (GIST’s) are the most common mesenchymal neoplasms of the gastrointestinal tract. Majority of the GISTs are asymptomatic and often diagnosis is incidental. Synchronous second malignancies have been reported in patients with GIST. We report a case of 50-year-old female presenting with features of hollow viscous perforation, found to have ileal GIST with perforations along with a synchronous breast sarcoma. GIST with spontaneous perforation as its first clinical manifestation is rare. Synchronous occurrence of an ileal GIST with a breast sarcoma is unique and deserves reporting. This case report highlights the varied nature of clinical presentation of the GIST and also stresses on the importance of extensive search for the synchronous second malignancies in the extra abdominal sites as well.